Patients treated with first‐generation HCV protease inhibitors exhibit high ribavirin concentrations. (4th February 2015) - Bodeau, Sandra; Nguyen‐Khac, Eric; Solas, Caroline; Bennis, Youssef; Capron, Dominique; Duverlie, Gilles; Brochot, Etienne
Abstract Anemia is a well‐known RBV‐related event in HCV therapy which is exacerbated by the addition of telaprevir and boceprevir. This retrospective study evaluated and compared ribavirin exposure and parameters able to influence hemoglobin decrease in a large population of patients treated with dual or triple therapy. Patients on triple therapy had higher ribavirin concentrations at week 12 of treatment (3460 ng/mL vs. 1843 ng/mL; P < .0001). An association was also observed between week 12 eGFR and ribavirin concentration only for patients on triple therapy (P = .002). The proportion of patients with a >20 mL/min/1.73 m2 decrease in eGFR at week 12 was higher among patients on triple therapy: 32%, 14%, and 5% for boceprevir, telaprevir, and dual therapy, respectively (P = .025 and .026). No correlation was observed between boceprevir and telaprevir concentrations and hemoglobin or eGFR decrease. Exacerbation of anemia in patients on triple therapy is related to higher ribavirin concentrations. We provide an explanation for this increase in plasma RBV concentration. Triple therapy with PEG‐IFN, RBV, and telaprevir or boceprevir will remain the only HCV treatment option for many patients. Our data show that the RBV dose can be decreased while maintaining adequate plasma concentrations and reducing anemia.